Nathan Fellows Dixon family papers - Dixon, Nathan Fellows, 1774-1842.; Dixon, William
Copies of legal documents covering land and business transactions, visiting cards, manuscript of William Dixon, and other papers relating to the Dixon family of Westerly, R.I.
Lawyer, banker, state legislator, U.S. senator from Rhode Island.
Collection material in English.
Keywords: Dixon family; Rhode Island -- Social life and customs; Westerly (R.I.) -- Social life and customs; Bankers; Lawyers; Legislators -- Rhode Island; Senators, U.S. Congress -- Rhode Island